SOSIALISASI MANFAAT AKUNTANSI UNTUK MENINGKATKAN PENGETAHUAN PARA PEDAGANG KAKI LIMA DI STADION WERGU WETAN KUDUS - Febra Robiyanto; Dennyca Hendriyanto Nugroho (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Every business or business actor has one goal in running the business. This goal has a broad scope, various efforts will be made to get a profit. One effort that can be done is to create management control so that the company can operate efficiently and effectively. An entrepreneur must have a good strategy to take advantage of existing strengths and opportunities, as well as cover weaknesses and overcome obstacles faced in the business world. In carrying out a business, financial information or financial management is needed in the form of preparing a budget in the form of financial reports. The purpose of this training activity is to provide knowledge about the benefits of accounting to street vendors at Bangkalan Stadium with the target being the formation of a social order that carries out a financial reporting preparation system. they are concerned with managing or compiling difficult financial reports and it is hoped that the businesses at the Bnagkalan Stadium can increase sales through the preparation of a financial budget. The implementation method that will be used in this service program is through the provision of socialization regarding accounting in the form of training in preparing simple financial reports in order to increase the accounting knowledge of street vendors at Bangkalan Stadium. In this implementation method is divided into three stages, namely preparation, implementation and reporting